Estimating the effect of accessibility on wages - Knudsen, Elias Stapput; Hjorth, Katrine; Pilegaard, Ninette (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
In this paper, we estimate the elasticity of wages in Denmark with respect to changes in generalised travel costs. The estimation of the elasticity is done on Danish register data from year 2002 and 2010. This elasticity is used as an estimate for the productivity effects of transport infrastructure changes and is to be applied in calculations of the wider economic benefits of transport infrastructure improvements in Denmark.